Advancing environmental sustainability of ceramic tile production: a cradle-to-gate life cycle assessment case study from Sri Lanka - Vijerathne, Dimuthu Thisna; Wahala, Sampath Bandara; Asmone, Ashan Senel (Frontiers in Built Environment, 2025)
IntroductionEnvironmental sustainability in the ceramic tile industry has gained global attention due to its significant impact on the building and construction sector. Sustainable production strategies are critical to reducing environmental footprints while maintaining economic growth.MethodsThis study evaluates and compares the environmental impacts of conventional ceramic tile production with four proposed eco-innovation scenarios using a cradle-to-gate life cycle assessment (LCA) approach. Environmental impacts were quantified per square meter of gross floor area of ceramic tile using SimaPro Faculty version. All four eco-innovation scenarios were compared against the conventional (base) scenario. Scenario 1 partially replaces virgin raw materials with waste materials (e.g., fly ash). Scenario 2 focuses on energy recovery for heating during the drying process. Scenario 3 substitutes conventional energy sources with cleaner alternatives. Scenario 4 integrates all these eco-innovative strategies.ResultsThe analysis indicates that human carcinogenic toxicity is the most critical environmental impact across all five scenarios. Among the eco-innovation alternatives, Scenario 4 emerges as the most sustainable, achieving a 26.73% reduction in terrestrial acidification, a 23.23% decrease in stratospheric ozone depletion, and a 21.36% reduction in global warming potential compared to the baseline scenario.DiscussionThese findings provide valuable insights for policymakers and ceramic manufacturers in Sri Lanka, supporting the development of sustainable strategies to enhance environmental performance. By integrating renewable energy, waste materials, and energy-efficient technologies, the ceramic tile industry can transition toward more sustainable production, striking a balance between economic growth and environmental stewardship. This research addresses local challenges and contributes to global efforts in sustainable manufacturing, setting a precedent for other industries.